Klasterisasi Staphylococcus aureus Resisten Neutrofil Berdasar Assesory Gene Regulator - Santosa, Christin Marganingsih; Lestari, Fajar Budi; Widayanti, Rini; Salasia, Siti Isrina Oktavia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Staphylococcus aureus is recognized worldwide as a major pathogen causing subclinical intramammary infections in dairy cows and food poisoning due to its ability to produce enterotoxin. The study aimed to identify enterotoxins of S. aureus and clustering the enterotoxins based on assessory gene regulator (agr). Virulence of S. aureus to the host was characterized based on the response of polymorphonuclear cells to the infection. Twelve S. aureus could be isolated from milk cows in central of dairy farming in Sumedang West Java. The identification of S. aureus was based on cultural and biochemical tests and an amplification of a specific section of the 23S rRNA gene. The sensitivity test against antibiotics revealed that some isolates of S. aureus were resistant to penicillin and methycillin. By PCR amplification one or more staphylococcal enterotoxin genes could be observed five genes in combinations of sea (216 bp), seb (478 bp), seh (375 bp), sei (576 bp), and sej (142 bp). Clustering of S. aureus based on the assesory gene regulator could be grouped into 4 clusters for agr1 (1 isolat), agr2 (2 isolates), in combination for agr1 and agr2 (1 isolate), and for non agr (2 isolates). Based on the response of polymorphonuclear cell in vitro and in vivo assays, revealed that S. aureus strain I-2 (agr1 cluster) and P1 (agr1+agr2 cluster) were more resistant to polymorphonuclear cells and could survive intracellularly, indicated that these strains could be used as proper candidates to develop dignostic tool based on agr against staphylococcal mastitis.